Comparison between Effects of Ketofol and Dexmedetomidine as Sedative in Elective Caesarean Section under Subarachnoid Anaesthesia (Bangladesh Critical Care Journal, 2023)
Background: Regional anaesthesia has become an important anaesthetic technique now a days. The use of spinal(subarachnoid) anaesthesia is often limited by the unwillingness of patients to remain awake during surgery.Pharmacologically induced tranquility improves acceptance of regional technique.Objective: This study compares Ketofol (Ketamine + Propofol) and Dexmedetomidine in terms of onset and recovery ofsedation, haemodynamic effects, respiratory effects and adverse effects of both the drugs during elective Caesariansection under spinal anaesthesia.Materials and Methods: This randomized clinical trial included 60 ASA (American Society of Anaesthesiologists)grade I and II patients between age 20-40 years undergoing elective Caesarean sections under Subarachnoidanaesthesia during the period January 2022 to June 2022. Patients were randomly allocatedto one of two groups:Ketofol group (Group KP, n=30), who received Ketofol in a single dose of 0.5mg/kg (Ketamine-0.5mg/ kg+Propofol-0.5mg/kg) and Dexmedetomidine group (Group D, n=30), who received Dexmedetomidine in a single dose of 2mcg/kg.Spinal anaesthesiawas conducted by injecting a hyperbaric solution of 0.5% bupivacaine 3ml through a 25G spinalneedle at L3-4 level. All parameters were documented at 5 min intervals until arousal of the patient. The onset ofsedation i.e. time from iv (intravenous) injection of Ketofol or Dexmedetomidine to closure of eye lids (OAA/S score of3) and the arousal time from sedation i.e. time from closing of the eye lids to OAA/S score of 5 ( patient is awakeclinically) were noted. Any complication during operation was documented. Patient’s satisfaction with the sedation wasassessed by the 5 point ‘Likert verbal rating scale’.Results: There was no significant difference of mean blood pressure and mean heart rate between the two groups indifferent time intervals (P>0.05). Time of onset of sedation was significantly delayed in Dexmedetomidine group(P0.05). Ketofol wasassociated with significantly higher incidence of some adverse effects like pain in arm during drug administration thanDexmedetomidine (33.33% vs 10%, P